Guide to CFO success : leadership strategies for corporate financial professionals - Dergel, Samuel, 1969- (Hoboken, N.J. : Wiley, 2014)
Proven leadership strategies that will impact your career and your company Having the right CFO is a critical component for every company's success. Guide to CFO Success provides CFOs and those in the making with a strategic blueprint to benefit their companies and their careers. This book reveals how to build a strong, successful career plan with guidance on team building and management of the multiple relationships that CFOs face on a daily basis, plus how to balance one's work and personal life. Offers strategic guidance for leadership growth for CFOsPresents essential information for every.
Goal Setting and the Path to Success.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Chief financial officers; Career development; Investments -- Social aspects; Social responsibility of business; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Career development; Chief financial officers; Electronic books